ANALISIS EFEKTIVITAS PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PAD PROVINSI YANG ADA DI PULAU SUMATERA - Seventeen, Winny Lian; Purnamasari, Bunga (Universitas Prof.Hazairin,SH Bengkulu, 2023)
This research was conducted to analyze the effectiveness of local taxes and levies on increasing PAD in the provinces of Sumatra Island. This type of research is qualitative with a descriptive analysis approach. The types of data are qualitative and quantitative data. The data analysis method used in this research is the Descriptive Analysis method. In addition, this study also uses quantitative analysis used in calculating the effectiveness of local taxes and local levies on increasing PAD. The results showed that out of 10 provinces, 9 provinces were categorized as very effective, while 1 province, Bengkulu, indicated an effective achievement although it did not exceed the target significantly at 93.29%. Research on the effectiveness of local retribution, there are 2 provinces with a very effective level of effectiveness, namely Aceh and South Sumatra. 3 provinces namely, Riau, Jambi and Lampung have an effectiveness level with a less effective category, while 5 other provinces have an effectiveness level with an ineffective category.